Libraries, archives, and museums today insights from the field - Botticelli, Peter, 1966-; Mahard, Martha R., 1948-; Cloonan, Michèle Valerie, 1955- (Rowman & Littlefield, 2019)
This book explores the intersections among libraries, archives, and museums (LAMs) in such practices as digital content creation, conservation and preservation, collections cataloging, digital asset management, digital curation and stewardship, expanding user experiences, and cultivating digital cultural communities.